การศึกษาวิเคราะห์ผลระยะยาวของวัสดุเคลือบอนุภาคนาโนแคลเซียมคาร์บอเนตและเซลลูโลสพอลิเมอร์ต่อสมบัติและการเสื่อมสภาพของกระดาษด้วยการบวนการเร่งอายุ - เมฆมุกดา ชลิตา (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2022)
Paper has been used as main writing and printing carrier for storing human history and knowledge. However, paper deteriorates overtime due to the generated acidity. Cellulose chains are depolymerized by acid-hydrolysis and the consequences are yellowing and massive loss of mechanical strength of paper. In this project, an organic solvent-based process using a polysaccharide derivative and alkaline nanoparticles for the simultaneous deacidification and strengthening of paper has been developed. Colloidal dispersion of CaCO3 nanoparticles (size ca. 100 nm) stabilized by ethyl cellulose in ethanol was employed to reduce acidity and strengthen the paper. The treatment was performed impregnating the old acidic papers with the dispersion. Various techniques of analysis showed a good distribution of CaCO3 nanoparticles on cellulosic fiber of papers. The papers were successfully neutralized from pH of 5 to pH of 7, inhibiting the degradation of papers. Moreover, the mechanical properties of papers were improved due to the surface coating of ethyl cellulose polymer. Lastly, aging test confirmed that the degradation of papers could be delayed by treatment with the developed process.